Two distinct interferon-γ genes in Tetraodon nigroviridis: Functional analysis during Vibrio parahaemolyticus infection. (February 2016) - Peng​, Wan; Lu, Dan-Qi; Li, Gao-Fei; Zhang, Xu; Yao, Mi; Zhang, Yong; Lin, Hao-Ran
Highlights: Upon Vibrio parahaemolyticus infection, IFNγ1 and IFNγ2 perform different functions. This study is the first to demonstrate the involvement of miR-29b in the response to Vibrio parahaemolyticus infection. This study is the first to provide evidence of a relationship between the expression of miR-29b and IFNγ2 in fish undergoing an in vivo challenge. Abstract: Interferon gamma (IFNγ) is a Th1 cytokine that plays a very important role in almost all phases of immune and inflammatory responses. In this study, we explored the functions of IFNγ1 and IFNγ2 of Tetraodon nigroviridis . Treating T. nigroviridis spleen and head kidney cells in vitro with recombinant T. nigroviridis IFNγ1 protein (r Tn IFNγ1) or recombinant T. nigroviridis IFNγ2 protein (r Tn IFNγ2) enhanced their nitric oxide responses. Both r Tn IFNγ1 and r Tn IFNγ2 also induced the expression of interferon-stimulated gene 15 (ISG15), a common anti-viral gene, although the expression of the interferon-inducible Mx gene was markedly inhibited by r Tn IFNγ1 and was induced by r Tn IFNγ2. The in vivo effects of r Tn IFNγ1 and r Tn IFNγ2 on Vibrio parahaemolyticus ( V. parahaemolyticus ) infection were assessed by intraperitoneally injecting r Tn IFNγ1 or r Tn IFNγ2 (100 ng) and V. parahaemolyticus (8 × 10 10 CFU/mL) into T. nigroviridis. A comparison of the group treated only with V. parahaemolyticus and those also treated with r Tn IFNγ1 or r Tn IFNγ2 showed that neither of these IFNγs protected T. nigroviridis from V. parahaemolyticus infection. However, r Tn IFNγ1 more rapidly and robustly promoted inflammatory responses compared with r Tn IFNγ2, whereas r Tn IFNγ2 was involved in inducing the host to develop a more effective response earlier during the later stage of a V. parahaemolyticus infection. Moreover, microRNA-29b (miR-29b) expression is inversely correlated with IFNγ2 expression in T. nigroviridis .